2016
DOI: 10.1007/s00170-016-9276-y
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of machining errors of Bspline and Cspline

Abstract: The high-speed milling operation is widely used in industry for the production of aircraft parts, molds, and dies. The machining based on the polynomial programming (especially Bezier or basic spline (Bspline) and cubic spline (Cspline)) brings an interesting gain in cycle time. However, part quality can be degraded by using this type of programming. In this paper, we suggest a simulation methodology for errors caused by the interpolations: Bspline and Cspline in high-speed machining of warped shapes. To do th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The CAD and CAM systems spline bases are usually unknown for the user. In other works, such as [29], the interpolation algorithm had to be experimentally extracted to simulate the interpolation errors. In this work, the interpolation errors were calculated graphically in the CAM program.…”
Section: Analysis Of the Curve Fitting Errorsmentioning
confidence: 99%
“…The CAD and CAM systems spline bases are usually unknown for the user. In other works, such as [29], the interpolation algorithm had to be experimentally extracted to simulate the interpolation errors. In this work, the interpolation errors were calculated graphically in the CAM program.…”
Section: Analysis Of the Curve Fitting Errorsmentioning
confidence: 99%
“…After the simulation of machining errors of the interpolations, Bspline and Cspline [2], our choice was oriented towards the method of the node insertion, in order to compensate the machining errors. It consists of adding nodes in the toolpath as a means to respect the proposed tolerance.…”
Section: Principlementioning
confidence: 99%
“…Among these interpolations object of the study, we find the polynomial or spline functions (NURBS, Bspline). Our previous research [1,2] has shown the influence of the interpolation type, such as the functions: Bspline and Cspline, on the machining errors in HSM of a free form (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the nonuniform rational B-spline, an adaptive mathematical expression model was established to describe the spatial errors of machine tools. El Bechir et al [10] suggested a simulation methodology for errors caused by the interpolations B-spline and C-spline in high-speed machining of warped shapes and developed analytical models expressing the basic paths of the interpolations. In 2017, Chen et al [11] attempted to establish an error model of 12 terms of polynomial in total for the triaxial linkage of machine tools based on the error measurement data of the whole working space of machine tools and preliminarily discussed the error prediction method for the points at different spatial locations of machine tools.…”
Section: Introductionmentioning
confidence: 99%